Analyzing Qualitative Data with MAXQDA - Kuckartz, Udo; Rädiker, Stefan (Springer, 2019)
“To begin at the beginning” is the opening line of the play Under Milk Wood by Welsh poet Dylan Thomas. So, we also want to start here at the beginning and start with some information about the history of the analysis software MAXQDA. This story is quite long; it begins in 1989 with a first version of the software, then just called “MAX,” for the operating system DOS and a book in the German language. The book’s title was Text Analysis Software for the Social Sciences. Introduction to MAX and Textbase Alpha written by Udo Kuckartz, published by Gustav Fischer in 1992. Since then, there have been many changes and innovations: technological, conceptual, and methodological. MAXQDA has its roots in social science methodology; the original name MAX was reference to the sociologist Max Weber, whose methodology combined quantitative and qualitative methods, explanation, and understanding in a way that was unique at the time, the beginning of the twentieth century. Since the first versions, MAX (later named winMAX and MAXQDA) has always been a very innovative analysis software. In 1994, it was one of the first programs with a graphical user interface; since 2001, it has used Rich Text Format with embedded graphics and objects. Later, MAXQDA was the first QDA program (QDA stands for qualitative data analysis) with a special version for Mac computers that included all analytical functions. Since autumn 2015, MAXQDA has been available in almost identical versions forWindows and Mac, so that users can switch between operating systems without having to familiarize themselves with a new interface or changed functionality. This compatibility and feature equality between Mac and Windows versions is unique and greatly facilitates team collaboration. MAXQDA has also come up with numerous innovations in the intervening years: a logically and very intuitively designed user interface, very versatile options for memos and comments, numerous visualization options, the summary grid as a middle level of analysis between primary data and categories, and much more, for instance, transcription, geolinks, weight scores for coding, analysis of PDF files, and Twitter analysis. Last but not least, the mixed methods features are worth mentioning, in which MAXQDA has long played a pioneering role.
Text, Audio, and Video